PLC: literature survey and poster presentation / Siti Noratna Rashid - Rashid, Siti Noratna (2000)
Automatic control has become an important consideration in most industrial processes where certain repetitive operations are performed. This applies to situation such as the automatic assembly of modules and products where cycles of event are conducted in a consistent and uniform manner. An application generally includes a combination of feeding, handling, drilling, cutting, assembling, discharging, inspecting, packaging and transporting by conveyer. Prior to the introduction of computer based control systems the automaton of such event was achieved by using either electrical relay logic circuits or pneumatic logic circuit. Although these are conception ally simple and easy to maintain they are somewhat bulky and can be expensive. More important is the fact that the resulting control circuits are inflexible and do not lend them to easy system control alteration .In late 1960s saw the introduction of the programmable logic controllers (PLC) as a direct replacement for the relay sequence controllers. In essence the PLC replace the hardwired relay or pneumatic logic with a more flexible programmable logic. It offers a simple, flexible and low cost means of implementing a sequence control strategy where outputs for switching devices on and off are set according to input conditions as read from digital sensor state.